HUBUNGAN ANTARA PEMBAGIAN ZAKAT, INFAQ, DAN SEDEWA DENGAN TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs) - Pohan, Syahrial Hasanuddin; Rianto, Hartato; Lubis, Sakban (Seminar Nasional Sosial Sains dan Teknologi Halal; 2021, 2022)
This study analyzes the practice of distributing Islamic philanthropic funds carried out by the IZI representative office and Dompet Duafa, Medan City. This study aims to determine the alignment of the implementation of the Islamic philanthropic fund distribution program carried out by the IZI representative office and Dompet Duafa Medan City with seventeen Sustainable Development Goals (SDGs). The research method used is a comparative qualitative model where researchers will compare the islamic philanthropy fund distribution program with the sustainable development goals (SDGs). The results of this study show that the implementation of the distribution of Islamic philanthropic funds carried out by IZI and Dompet Duafa Medan City is in line with eight sustainable development goals (SDGs), namely No Poverty; No Hunger; Healthy and Prosperous Living; Quality of education; Clean Water and Proper Sanitation; Decent Jobs and Economic Growth; Reducing Inequality; Partnerships to Achieve Goals.